The Mediating Role of Non-reactivity to Mindfulness Training and Cognitive Flexibility: A Randomized Controlled Trial - Zou, Yingmin; Li, Ping; Hofmann, Stefan G.; Liu, Xinghua (Frontiers in Psychology, 2020)
Mindfulness training has a beneficial effect on cognitive flexibility. However, little is known about the mediators that produce this effect. Cross-sectional studies show that there might be a link between non-judgment, non-reactivity and cognitive flexibility. Longitudinal studies examining whether non-judgment or non-reactivity mediate the effectiveness of mindfulness training on improving cognitive flexibility are lacking. The present study aims to test the efficacy of mindfulness training on increasing cognitive flexibility and to test whether this effect is mediated by non-judgment or non-reactivity. We conducted a single-blind randomized controlled trial in 54 nonclinical high-stress participants between October 2018 and January 2019. Participants were randomly assigned to a Mindfulness Based Stress Reduction (MBSR) group or a waitlist control group. The experimenters were blind to the group assignment of participants. The MBSR group received 8-week (2.5-hour per week) sessions and a one-day retreat (6-hour), and was required to accomplish a 45-min daily formal practice during intervention. The waitlist control group did not receive any intervention during the waiting period and received 2-day (6-hour per day) mindfulness training after the post-intervention. The primary outcome was self-report cognitive flexibility and perceived stress. They were administered at 2 time points: pre- and post-intervention of the MBSR group. The secondary outcome was self-reported mindfulness skills (including non-reactivity and non-judgment). They were measured at 4 time points within the entire period of the MBSR training: pre-intervention, Week 3, Week 6 and post-intervention. For cognitive flexibility, mixed-model repeated-measure ANOVA results showed that there were significant main effects of Time, Group and a significant interaction of Time by Group. Follow-up ANOVA indicated that the MBSR group had greater improvements in cognitive flexibility than the waitlist. Path analysis results showed that the effect of the treatment on cognitive flexibility at post-treatment was fully mediated by non-reactivity at Week 6. The mediation effects of non-reactivity at Week 3, and non-judgment at Week 3 or Week 6 were not significant. Our findings support the efficacy of MBSR on improving cognitive flexibility. Non-reactivity is an important element of the effectiveness of MBSR training on cognitive flexibility.